Joseph Schacht and the Early Concept of Islamic Law Formation: A Study of Orientalist Perspectives - Annisa Az Zahra; Gina Sabila; Khulda Azizah; Noor Khalisah; Muhammad Anshari; Anwar Hafidzi (PT. Sharia Journal and Education Center, 2024)
Joseph Schacht, a leading orientalist, is known for his analysis of Islamic law using historical and sociological approaches. In his view, Islamic law is not merely a set of directly revealed norms, but the result of a proc ess of historical development that is closely related to the social dynamics of Muslim society. Through extensive research, he argues that many hadith were composed or modified to support the development of Islamic law at particular times. In his view, the peak of the formation of Islamic law occurred during the time of Imam al-Shafi'i, who succeeded in systematizing the methodological framework of Islamic law. Some scholars consider his ideas to provide new insights into the development of Islamic law, while others consider his approach to be reductionist and ignores the spiritual and theological dimensions of Islamic law. Despite the controversy, Schacht's thought remains one of the important references in modern Islamic legal studies.